The Urgency of Reformulating Regulations on the Postponement of Marital Property Distribution to Fulfill the Best Interests of the Child - Fatahillah, Zahrul; Ilham, Ajhatul; Mansari; Azharuddin (Universitas Islam Negeri Ar-Raniry, 2026)
The regulation of the distribution of marital property in Indonesia has not yet incorporated a child-protection perspective. In fact, divorce has direct consequences for children, particularly in situations where the marital property consists of only a single asset, namely the family home. If such property is divided equally between the husband and the wife, it may result in adverse effects on the best interests of the child. This study aims to analyze the urgency of reformulating the regulation of marital property distribution in a manner oriented toward child protection and the best interests of the child as reflected in Supreme Court Circular Letter (SEMA) Number 1 of 2022. This research employs a normative legal research method. The legal materials used consist of the Marriage Law and the Compilation of Islamic Law. Data collection was carried out through a literature review of library materials. The data were analyzed descriptively and prescriptively. The findings indicate that reformulating the regulation on postponing the distribution of marital property in the form of legislation is essential to address the existing legal vacuum in Indonesia. Although the Supreme Court has issued an internal policy in the form of a SEMA, its effectiveness is weak because it functions merely as an internal directive that is not legally binding on judges. A provision acquires binding force only when it is regulated in statutory legislation. The SEMA has attempted to realize the best interests of the child by providing for the postponement of the distribution of marital property when the property acquired during the marriage consists solely of a house that serves as the family residence. Dividing the house equally between the husband and the wife may generate negative consequences for the child, as the child could lose their place of residence.